An institutional and stakeholder perspective of governance, ethics and trust in State Operated Enterprises - Manda, More Ickson (University of the Witwatersrand, Johannesburg, 2023)
State-Operated Enterprises (SOEs) in South Africa continue to face significant challenges impacting their performance. Governance and other ethical concerns have been identified as factors that have impacted the performance of SOEs. Consequently, trust in SOEs among stakeholders such as the state, business, civil society, and citizens has been eroded. This study explores corporate governance in SOEs using an institutional and stakeholder perspective to examine the relationship between trust, corporate governance, and ethics in institutions. The study is a quantitative study that uses a survey as its primary method of collecting data. Findings were triangulated with evidence from documents and literature. The study was conducted in South Africa, a middle-income developing country and young democracy confronted by many challenges, such as corruption, decreasing public trust and investor and businessconfidence. This has spotlighted theoretical and practical issues such as corporate governance. The study proposed a framework for strengthening trust and corporate governance to restore legitimacy in institutions, an essential factor in building strong, responsible, and capable institutions that deliver value to shareholders and stakeholders. The study also made practical recommendations for strengthening ethics, governance, and trust
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: corporate governance; UCTD; Stakeholder theory; Institutional theory; SOEs; Trust; Ethics; Ethical leadership; Corporate social responsibility; SDG-8: Decent work and economic growth